Supplement usage and doping attitudes in elite youth sports: The mediating role of dietary supplement acceptance - Kristensen, J. Å.; Haugen, T.; Ommundsen, Y. (PLOS ONE, 2024)
This study investigated whether dietary supplement acceptance mediated the relationship between supplement use and doping attitudes in youth sports. To this end, we employed a two-wave half-longitudinal design during a sports season (time point one [T1] to time point two [T2]). The sample consisted of 217 elite youth athletes (47% male; mean age = 16.98 years, standard deviation = 0.88) who competed in team sports (43%; N = 93; basketball, floorball, handball, and ice hockey) and individual sports (57%; N = 124; alpine skiing, biathlon, cross-country skiing, swimming, and tennis). The participants were recruited from eight Norwegian sports academy high schools that provide extracurricular, higher-level training and specialization for youth athletes. Results from structural equation modeling analysis indicated that dietary supplement acceptance (T2) mediated the positive relationship between supplement use (T1) and doping attitudes (T2) when accounting for prior levels of the mediator and the outcome variable. These findings suggest that when young athletes used dietary supplements at the start of the season to improve their performance, they were more likely to view the use of supplements as acceptable and to report more favorable attitudes toward doping at the end of the season six months later. For those seeking to prevent doping in youth sports, targeting athletes` views on the acceptable use of dietary supplements may be important.